Palace of deception : museum men and the rise of scientific racism - Lunde, Darrin P. (W.W. Norton & Company, 2025)
"From 1908 to 1933, the American Museum of Natural History launched more scientific field expeditions than at any other time in its existence. Sponsoring lavish trips to Africa and Central Asia, the museum filled its halls with artifacts and an aura of adventure, supported by some of New York City's most prominent men, including Theodore Roosevelt and J. P. Morgan. All the while, the museum's then president, Henry Fairfield Osborn, attempted to use his adventurers' expeditions to fulfill a personal agenda : to propagate his belief in racial hierarchy. Palace of Deception uncovers the complicated legacyof three iconic figures of the American Museum : the preeminent explorer Roy Chapman Andrews ; Carl Akeley, the pioneering taxidermist who created so many of the museum's most memorable exhibits ; and Osborn, the museum's president, who was once considered an authority on everything from paleontology and evolution to race and eugenics. From Andrews's ambitions searching for fossils in the Gobi Desert to the construction of Akeley's artistic masterpiece, the Hall of African Mammals, Darrin Lunde tells the story of the American's Museum foundational years. Lunde also shows how the achievements of the museum's adventurers were used to introduce residents of New York to a version of the natural world -- one full of strict natural laws and categories -- endorsed by the museum's powerful leader. Based on extensive diaries, letters, journals, and the author's own experiences leading modern-day expeditions to several of the same places, Palace of Deception re-creates some of the most celebrated, globe-trotting journeys from natural history's heyday. It also traces the larger, racially infused milieu that underwrote the golden age of exploration,uncovering the simmering anxieties about race behind the era's greatest adventures. It is a legacy that still haunts natural history institutions today."--